Digital Photography Hacks - Story, Derrick (O'Reilly, 2011)
Going beyond the standard fare of most digital photography books, Digital Photography Hacks shares the knowledge that professional photographers have learned through thousands of shots' worth of experience and years of experimentation. With exquisite, full-color photos throughout, the book presents 100 proven techniques in the areas of daytime and nighttime photo secrets, flash magic, digital camera attachments, fun photo projects, camera phone tricks, and more. This book is your passport to taking the kind of digital photos you've always aspired to.